Hubungan Aktivitas Fisik dan Pola Makan dengan Kejadian Obesitas pada Anggota Polri di Polda Kalimantan Tengah - Nelly Rohmatika; Hermanto Hermanto; Kristin Rosela (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2024)
Obesity is a major cause of diseases such as diabetes, heart disease, and other metabolic disorders. A preliminary study conducted on 15 police officers from the Central Kalimantan Police Department revealed that 9 officers (60%) were obese, while 6 officers (40%) were not. Among the 9 obese officers, 8 admitted to rarely engaging in regular physical activity and frequently consuming fast food, while 1 officer was in the process of losing weight by exercising and maintaining a healthy diet. The causes of obesity include physical activity and dietary patterns. The objective of this study was to analyze the relationship between physical activity and dietary patterns and the incidence of obesity among police officers at the Central Kalimantan Police Department. Methods: This correlational study used a cross-sectional approach to examine the relationship between physical activity and dietary patterns and the incidence of obesity among police officers at the Central Kalimantan Police Department. Data collection instruments included questionnaires and BMI measurements. The sample consisted of 196 police officers classified as overweight and obese, selected through simple random sampling. The data were analyzed using the Chi-Square correlation test. Results: The study found a significant relationship between physical activity (p-value = 0.000, 83.6%) and dietary patterns (p-value = 0.000, 73.8%) and the incidence of obesity among police officers at the Central Kalimantan Police Department. Conclusion: Physical activity and dietary patterns are significantly related to the incidence of obesity among police officers at the Central Kalimantan Police Department. The role of nurses in addressing obesity should begin with an accurate assessment of family care patterns, ensuring that interventions and education provided are effective, and prioritizing promotive and preventive measures to address obesity and prevent the emergence of chronic diseases.